Metalorganic solution deposition of lead zirconate titanate films onto an additively manufactured Ni-based superalloy. (1st January 2017) - Patel, T.; Khassaf, H.; Vijayan, S.; Bassiri-Gharb, N.; Aindow, M.; Alpay, S.P.; Hebert, R.J.
Abstract: Recent advances in additive manufacturing of high-temperature alloys for structural aerospace applications has led to interest in integrating additional functionality into such parts. Lead zirconate titanate (PZT) is a prototypical ferroelectric ceramic used as the electro-active material in many piezoelectric sensors and actuators. In this study, 300 nm thick PbZr0.2 Ti0.8 O3 (PZT 20/80) films were grown using metalorganic solution deposition onto additively manufactured substrates of Inconel 718. The microstructures of the films and the nature of the film/substrate interfaces were characterized using a combination of X-ray diffraction and electron microscopy techniques. Electrical measurements were performed to determine the ferroelectric, dielectric, and conductive responses of the PZT films. Our findings show that the PZT films exhibit robust ferroelectricity characterized by well-defined polarization-applied electric field ( P - E ) hysteresis loops. The samples display internal bias of up to ∼40 kV/cm. The room temperature remnant polarization and the small signal dielectric permittivity are ∼70 μC/cm 2 and 205, respectively. The dielectric loss (tan δ ) and the leakage current at 1 kHz are 9% and 1 nA at 1 V, respectively. We attribute the internal bias observed in the hysteresis loops and the overall large dielectric losses to the presence of an intermediate oxide layer at the PZT/Inconel interface, which forms during the high temperature crystallization of the ferroelectric film. These results show that it is possible to grow functional oxides with promising electrical properties onto additively manufactured metallic substrates. Graphical abstract: Image 1